INTERPRETATION OF EMOTIONAL STATES OF PERSONALITY IN THE WORKS OF JALALIDDIN RUMI - Alimbayeva Shaxlo Tursunovna; Solieva Dilnozahon Abduashimovna (American Journals Publishing, 2024)
This article describes the views of Jalaluddin Rumi on the human psyche, the psychological aspects of his scientific heritage, and also presents the interpretation of the emotional states of a person, described in the works "Masnaviyi manaviyi" and "Fihi ma fihi".
Keywords: Work, personal emotional states, heart, soul, mental processes.